Producer Companies in India : Potential to Support Increased Productivity and Profitability of Poor Smallholder Farmers - Leitch, Helen (World Bank Group, Washington, DC, 2015)
In 2002, the producer company model emerged to benefit poor farmers in India. This smart lesson, based on the World Bank's growing experience with producer companies in India, builds on lessons learned from the first and second Madhya Pradesh district poverty initiatives projects, which initiated 18 agriculture and livestock companies, involving 46,500 poor small farmers in over 1,550 villages in 14 districts - with 100 percent women shareholders in the livestock companies and 25 percent women owners in agriculture. Together, these 18 companies had an annual turnover of more than 9.5 million dollars in 2011-12.